A Case Report of Complete Excision of Brachial Plexus Schwannoma: A Rare Entity - Singh, Anish M; Singh, Janith L; Kayastha, Bellu; Shrestha, Prabin (Nepal Journal of Neuroscience, 2016)
Brachial plexus schwannomas are rare benign nerve sheath tumors and only about 5% of schwannoma arise from the brachial plexus. They create a great challenge to surgeons due to their rare occurrence and complex anatomical location. We present a case of 37 yrs female presented with a right supraclavicular mass with severe radiating pain in right hand. Further investigation was done with MRI and FNAC which turns out to be huge right brachial plexus schwannoma. Gross total resection was done without any neurological motor defi cits. Nepal Journal of Neuroscience. Vol. 13, No. 2, 2016, Page: 92-93